Optimizing the detection of N-nitrosamine mutagenicity in the Ames test - Heflich, Robert H.; Bishop, Michelle E.; Mittelstaedt, Roberta A.; Yan, Jian; Guerrero, Sharon K.; Sims, Audrey M.; Mitchell, Kamela; Moore, Nyosha; Li, Xilin; Mei, Nan; Elespuru, Rosalie K.; King, Sruthi T.; et al. (Regulatory toxicology and pharmacology, 2024)
Accurately determining the mutagenicity of small-molecule N-nitrosamine drug impurities and nitrosamine drug substance-related impurities (NDSRIs) is critical to identifying mutagenic and cancer hazards. In the current study we have evaluated several approaches for enhancing assay sensitivity for evaluating the mutagenicity of N-nitrosamines in the bacterial reverse mutagenicity (Ames) test. Preincubation assays were conducted using five activation conditions: no exogenous metabolic activation and metabolic activation mixes employing both 10% and 30% liver S9 from hamsters and rats pretreated with inducers of enzymatic activity. In addition, preincubations were conducted for both 60 min and 30 min. These test variables were evaluated by testing 12 small-molecule N-nitrosamines and 17 NDSRIs for mutagenicity in Salmonella typhimurium tester strains TA98, TA100, TA1535, and TA1537, and Escherichia coli strain WP2 uvrA (pKM101). Eighteen of the 29 N-nitrosamine test substances tested positive under one or more of the testing conditions and all 18 positives could be detected by using tester strains TA1535 and WP2 uvrA (pKM101), preincubations of 30 min, and S9 mixes containing 30% hamster liver S9. In general, the conditions under which NDSRIs were mutagenic were similar to those found for small-molecule N-nitrosamines. •12 small molecule nitrosamines and 17 NDSRIs were assessed for mutagenicity in the Ames test.•A combination of TA1535 and WP2 uvrA(pKM101) was able to detect all mutagenic nitrosamines.•In general, preincubations with 30% S9 produced higher mutagenic responses than 10% S9.•In general, hamster liver S9 produced higher mutagenic responses than rat liver S9.•Factors affecting assay sensitivity were similar for NDSRIs and small molecule nitrosamines.